Determinasi Opini Audit Going Concern - Puspita, Dea; Dirgantari, Novi; Wahyuni, Sri; Pandansari, Tiara (Owner : Riset dan Jurnal Akuntansi, 2024)
Going concern audit opinion is an opinion issued by the auditor to the auditee to determine whether the company can maintain its survival. A going concern audit opinion represents a negative signal for the company’s survival. Therefore, if a company is declared as going concern, it means that the company is declared capable of maintaining its business continuity. The aim of this research is to determine the influence of the pervious year’s audit opinion, auditor reputation, company growth and profitability on going concern audit opinion. The objects in this research are mining companies listed on the Indonesia Stock Exchange in 2016-2022. This type of research is quantitative research in the form of secondary data sourced from each company’s website and through the official IDX website. The sample in this research is mining companies listed on the Indonesia Stock Exchange in 2016-2022. The data collection technique used side purposive, which then obtained a sample of 34 companies. In this research, logistic regression analysis was used to analyze research data. The result of the test showed that the previous year’s audit opinion had a significantly positive effect on going concern audit opinion. The auditor reputation and company growth don’t have a significant effect on going concern audit opinion. Meanwhile, profitability has a significant negative effect on going concern audit opinion.